Genocide, geopolitics and transnational networks : con-textualising the destruction of the Union Patrotica in Colombia - Gomez-Suarez, Andrei (New York, NY : Routledge, 2015)
'This volume seeks to uncover and discuss the links between genocide, geopolitics and transnational networks'--
Includes bibliographical references (pages 192-208) and index.
Keywords: Political parties -- Colombia; Victims of state-sponsored terrorism -- Colombia; Genocide -- Colombia; State-sponsored terrorism -- Colombia